DISTRIBUSI LOGAM MERKURI PADA SEDIMEN LAUT DI SEKITAR MUARA SUNGAI POBOYA - Purnawan, Sandi; Sikanna, Rismawati; Prismawiryanti, Prismawiryanti (Natural Science: Journal of Science and Technology, 2013)
An investigation about Mercury metal content in marine sediment around Poboya stream has been done. The sediment samples were collected at 5 points of Poboya stream with 0; 15 and 30 days of time variations. The physical conditions of the water was analyzed i.e pH, temperature and salinity. The result showed that the lowest and the highest Mercury metal content (0,0103 and 0,185 mg/Kg) were found at point E and C respectively. It was found at the second and the first sampling accordingly. There was no significant increase of Mercury accumulation by time. In general, the Mercury metal content in the sediment around Poboya stream was still under government rule.